A Multi‐Parametric Fluorescent Assay for the Screening and Mechanistic Study of Drug‐Induced Steatosis in Liver Cells in Culture. Issue 1 (13th February 2018) - Tolosa, Laia; Gómez‐Lechón, M. José; Donato, M. Teresa
Abstract: Human hepatic cells have been used for drug safety risk evaluations throughout early development phases. They provide rapid, cost‐effective early feedback to identify drug candidates with potential hepatotoxicity. This unit presents a cell‐based assay to evaluate the risk of liver damage associated with steatogenic drugs. Detailed protocols for cell exposure to test compounds and for the assessment of steatosis‐related cell parameters (intracellular lipid content, reactive oxygen species production, mitochondrial impairment, and cell death) are provided. A few representative results that illustrate the utility of this procedure for the screening of drug‐induced steatosis are shown. © 2017 by John Wiley & Sons, Inc.